Tożsamość człowieka z etycznego punktu widzenia - Ślipko, Tadeusz (Horyzonty Wychowania, 2017)
Taking up the subject of man’s identity from ethical point ofview, the author, to begin with, explains the concept of „identity”from various points of view as presented by various scientificdisciplines: psychology, marxist philosophy, christian philosophy.As a consequence, he distinguishes „essential identity”, fundamentalfor ethical reflections of the subject and man’s „individualidentity”. Elaborating on the issue, according to christian philosophy,he defines man as a „human being”, who is the dynamicsubject of his own rational activity. Then, the author deals withthe problem of freedom as a category which determines hisidentity. Psychological freedom, the basic one, makes man reachdecisions about acting or non-acting, about the choice betweenright and wrong, which leads to the tense ambivalence in choice.However, only moral perception of freedom makes that man,ascending in transcendental sphere, aims for perfection, modelledon the objective order of moral values rooted in rationalnature. This is how human freedom assumes a form of moralfreedom based on moral order full of nobleness and stability. It isalso how the essence of man’s identity is expressed. The authorends with a statement that: „Closer to objective truth is the conceptionof man creating his own individual identity through creativemoral deeds, according to their objective exemplars, ratherthan via the spirit of philosophical existentialism, searching foridentity in the world deprived of moral signposts”.